Becoming aware of our environment: Poly Royal, April 25-26, 1975 (1975)
Front of poster: (L -> R) 1. The symbolical unit of man's living environment is the home. Yet man's home may extend from his house to this earth. It is this study which is the purpose of the School of Architecture and Environmental Design. 2. The School of Science and Mathematic exposes students to the fundamental concepts that govern the physical, mathematical and biological processes in our universe. The number six, which also forms the flask, denotes the interrelationship of science and mathematics with life and the environment. 3. As illustrated by the human figure, the School of Human Development and Education focuses on the growth of people. Human attitudes as well as physically growth are emphasized in producing a healthier environment. 4. As the fundamental working unit of machinery, the gear symbolizes the School of Engineering and Technology. The motion of the gear is analogous with this School's driving goal to provide a means to utilize economically the materials and forces of nature for the betterment of mankind. 5. The relationship of the human being to the environment is a major factor in the School of Communicative Arts and Humanities. The letter "a" symbolizes the beginning of the Arabic alphabet and a starting point of human recordings of meaningful encounters. 6. Studies of managerial structure work hand in hand with the knowledge gained toward advanced techniques and the search for innovations to create a more functional and pleasurable environment. The School of Agriculture and Natural Resources concerns itself with the existence of human beings and the production and growth of livestock and plants as represented by the tree. 7. The dollar sign portrays a basis of social existence, exchange, and distribution in a market economy. The School of Business and Social Science exposes students to social, economic, and political structures, management experiences, and human interaction. 8. As a symbol of an idea, the arrow represents the constant search for knowledge and achievement by expressing direction, movement, and excitement in "Becoming Aware of Our Environment" Back of Poster: (L -> R) Upper left hand corner ; shows illustrated map of SLO exits from the highway. Text to the right of the image reads, "Poly Royal is a time for sharing what Cal Poly means to us. We see it as a place to have good times and to acquire an education while being meaningfully involved in society. We want to share some of our good times with you this year when you participate with us. In addition, we are continually working towards making our world a better place to live. On exhibit during Poly Royal will be demonstrations of a car designed by engineering students to run solely on sewer gas, models by architecture students of building designs that require less fuel to heat and cool, and displays by virtually the whole university of what we are learning about our lives and our environment. Cal Poly is a unique experience and Poly Royal is the most memorable event of all. Poly Royal is planned and produced by students who care. Come to Cal Poly Royal April 25 and 26 and witness a panorama of environmental ideas that may influence your lives for years to come. (Upside down text): An Exhibition Through Awareness: The world we live in - our environment - is dynamic and ever changing. This year, the Poly Royal Board has chosen to focus on the present, and to show how we at California Polytechnic State University are "Becoming Aware of our Environment." In 1933, Cal Poly was a small campus far removed from the thriving town of San Luis Obispo. Each functioned in its own environment, and there was very little interaction between the two. Poly Royal began in that year to acquaint the community with the campus. Forty-three years later, we see the purpose of Poly Royal as unchanged. We think of ourselves as continually "Becoming Aware of Our Environment." Poly Royal started as "Country Fair on a College Campus" for students to practice showing their livestock prior to attending an important stock show in San Francisco. It featured, in addition to numerous displays, a barbecue and live night entertainment. Through the years, both Cal Poly and Poly Royal have [cuts off]. Major Events: Friday, April 25th: 10 am - Opening Ceremonies; High School Mathematics Contest; Symphonic Band Concert; Intercollegiate Rodeo; Intercollegiate Baseball; Concert Band Program; Intercollegiate Horse Show; University Singers and Chamber Orchestra; Student Carnival; Concert featuring Will Rogers, Jr. Saturday, April 26th: Pancake Breakfast; Poly 500 Soapbox Derby; Band and Vocal Performances; Barbecue Luncheon; Intercollegiate Rodeo; Powderpuff Football; Aquacade; Student Carnival; Tractor Rodeo; Western Dance A Unique Atmosphere The Community of San Luis Obispo is a blend of past and present. Founded over two hundred years ago as the fifth Franciscan mission in California, San Luis Obispo is located halfway between Los Angeles and San Francisco beside Highway 101. San Luis Obispo can easily recount the Spanish rancheros of the 1830's, Portuguese whalers and Italian-Swiss dairymen of the 1850's, and the Chinese railroad workers of the 1870's. Today San Luis Obispo is largely a result of a marked increase in student enrollment at Cal Poly beginning in 1945. San Luis Obispo is now the home of approximately 2,000 faculty and staff members, and 16,000 students and alumni. To the visitor, the community offers over 1,500 hotel and motel rooms, 50 restaurants, unique special interest shops, modern shopping malls, and numerous strategically-located service stations. Newly initiated bus lines connect various parts of the city for students, community members, and visitors. A Valuable Experience: Cal Poly can trace its beginning back to the Gold Rush of 1849. With the great influx of prospectors during this time, vocational skills were needed to build new communities. Myron Angel, a well-educated, yet penniless man arrived in San Francisco. He was unable to earn money due to his lack of manual skills, and therefor vowed that there should be an institution of learning devoted to training men and women in technical skills. Angel later became a San Luis Obispo newspaper publisher. His campaign for such a school became a reality in 1901 when the California State Legislature created a vocational high school at San Luis Obispo. The school was designed to train men and women in agriculture, engineering, commercial and domestic arts. Through its transition from a vocational high school to a degree-granting university, Cal Poly has never lost sight of its original commitment. California today has California Polytechnic State University, San Luis Obispo, a world leader in career education. More than 14,000 student receive career-oriented instruction in the seven schools which make up our curriculum at Cal Poly, In each of its fifty-two majors, students receive the best available classrooms and laboratory instruction. They are then able to apply this knowledge in related performance situations. Students raise crops and livestock, build structures, write and print publications, operate day-care nurseries, and in hundreds of other ways determine for themselves how their knowledge can be applied. Since the beginning, Cal Poly's faculty and students have worked together sharing knowledge and ideas. Upon graduation, Cal Poly students share their knowledge and abilities world-wide in a host of professions which touch the daily lives of people wherever they are aer. Cal Poly, one of nineteen campuses provides the opportunities for the students to put into practice the relationship of their classroom studies with their environment. An important aspect of our environment is the awareness people have of one another. A constant search of the needs and relationships [cutoff] ourselves and our surroundings is integral to our presentation. the simplicity of each design lends itself to the comprehension of a broader age bracket of people and to persons not familiar with the English language. The Individual designs were also created with a standardized format to complete a series of visually pleasing symbols easily identified through custom. As you your Poly Royal, these strategically-placed symbols will help direct and identify activities and events. Burt Sakai Susan Barkis